Entrepreneurial Orientation and Marketing Performance: The Mediating Role of Energizing Professional Networks - Riyoko, Sisno; Widodo, Widodo (SBM ITB, 2022)
Abstract. This article addresses the study controversy (research gap) of entrepreneurial orientation regarding marketing performance. The case study at hand, fashion SMEs, must present a distinct advantage due to intense competition. This advantage does not lie in how to create new products, but in how to build professional networks. Hence, the present article aims to develop a model for strengthening professional networks based on an entrepreneurial orientation to improve marketing performance. The population in this study comprises the leaders of fashion SMEs in Central Java, Indonesia. The sampling method employs a purposive 250 technique. The analysis technique uses SEM AMOS software. The results of the study show that proactiveness, risk-taking, and innovation have a significant and positive effect on professional network energy and marketing performance. In addition, the energy of professional networks mediates a strong relationship between proactiveness, risk-taking, and innovation in terms of marketing performance.Keywords: Proactiveness, risk-taking, innovativeness, energizing professional networks, marketing performanceAbstrak. Studi ini berdasarkan kontroversi studi (research gap) orientasi entrepreneur dengan kinerja pemasaran. Selain itu UKM Fashion harus memiliki keunggulan yang berbeda yang disebabkan persaingan yang ketat. Keunggulan yang dimaksud bukan bagaimana menciptakan produk baru tetapi bagaimana membangun profesional networks. Oleh karena itu artikel ini bertujuan untuk mengembangkan model penguatan jaringan profesional berbasis orientasi kewirausahaan untuk meningkatkan kinerja pemasaran. Populasi dalam penelitian ini adalah para pemimpin UKM Fashion di Jawa Tengah, Indonesia. Metode pengambilan sampel menggunakan teknik purposive 250. Teknik analisis menggunakan software SEM AMOS. Hasil studi menunjukkan bahwa proaktif, pengambilan risiko, dan inovasi memiliki efek yang signifikan dan positif pada energi jaringan profesional, dan kinerja pemasaran. Selain itu, energi jaringan profesional memediasi hubungan yang kuat antara proaktif, pengambilan risiko, dan inovasi pada kinerja pemasaran.Kata kunci: Proaktif, berani mengambil resiko, innovative, penguatan jaringan profesional, kinerja pemasaran.